A post Keynesian perspective on the eco zone project: Liquidity premia and external financial fragility in the West African Economic and Monetary Union, Ghana and Nigeria - Florian Lampe; Anne Löscher (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2021)
The paper treats the eco currency union project in West Africa and its implications for monetary policies against the backdrop of the international monetary order from a post-Keynesian perspective. The eco zone project envisions a common monetary union of the West African Economic and Monetary Union (WAEMU), i.e. the independent Western subzone of the CFA franc union, and the remaining non-CFA countries of the Economic Community of West African States (ECOWAS) with Nigeria and Ghana as the economically most important member states. The literature on the international currency hierarchy developed by Latin-American structuralists and the post-Keynesian Berlin School of thought focuses on the notion of a currency-specific liquidity premium that structurally determines the interest rate level in the corresponding currency areas. Based on this set of literature, we conduct a comparison between the liquidity premia of the Western CFA-franc, the Nigerian naira and the Ghanaian cedi to make conjectures about what implications a common ECOWAS currency union would have regarding monetary policy space. Being a non-pecuniary variable, the liquidity premium cannot be observed directly. We therefore approximate the liquidity premium by calculating differences in interest rates such as the central bank's base rate, the coupon rate on T-bills and bonds and the interest rate spread between Eurobonds and bonds denominated in local currency. Besides, we use balance of payment data to identify external financial fragilities that might become a crucial factor for monetary policy due to an increasing financialisation in West African economies. We find that investors demand structurally higher yields on bonds originating in Ghana and Nigeria than in the CFA-franc zone. One could interpret this as the CFA-franc conveying over a higher liquidity premium because it has to have lower yields rates to compensate for liquidity-differences to financial assets denominated in the US dollar or euro. However, another explanation is that expectations about the future developments of the cedi's and naira's exchange value by investors are more pessimistic in comparison to that of the CFA-franc. This is rooted in two major factors: Firstly, under the current arrangement, France still has leeway in monetary policy making and acts as exchange rate stabiliser by pushing for restrictive monetary policies and guaranteeing foreign exchange reserve provision. Secondly, the estimation of external financial fragility in the CFA-franc zone and Nigeria shows that the naira implies a greater risk of sudden devaluation due to a higher exposure to mobile liabilities vis-à-vis its asset endowments.
Keywords: E12; F33; F41; G11; O57; 330; West African Economic and Monetary Union; CFA franc; eco zone; international currency hierarchy; external financial fragility